Pengaruh Kekuatan Otot Lengan, Keseimbangan Dan Percaya Diri Terhadap Kemampuan Roll Depan Pada Senam Lantai - Kahar, Irsan; jalil, rasyidah; Nur, Suaib; hairati, Mifta; aldi, aldi (STAMINA, 2024)
The purpose of this study is to determine the influence of arm muscle strength, balance and confidence on the ability of the front roller on floor gymnastics of SMP Negeri 5 Palopo students. This study uses a quantitative approach and uses primary data through the distribution of questionnaires to students at SMP Negeri 5 Palopo. The population in this study was 25 student respondents with a sampling technique using proportional Random Sampling. The data was processed through the Spss version 23 program with correlation techniques and multiple linear regression analysis techniques. The results of this study show that there is a significant influence on the strength of the arm muscles, balance and confidence on the ability of the students' front rollers. Then the results of the f test prove that facilities and infrastructure simultaneously affect students' learning interest by seeing that the value of Fcal is greater than that of Ftable, which is (1,672>0,413) with a significance value of 0.010. The variable of muscle strength is the variable that has the greatest influence on the ability of students to roll in front of students at SMP Negeri 5 Palopo.